Poesia em sala de aula mediada pela intertextualidade e pelas TDIC - Carvalho , Soraya Souza de (2016)
This project was elaborated from the need to re-dimension the quality of the work with the reading of poetry, with the objective of promoting literary reading in an interactive way, promoting the integration of curricular content - reading and interpretation, through playful languages (reading Cinematographic, illustrations) and technological (oralized reading recorded and edited making use of technological tools such as cellular, computer and a reproductive medium, in the case a CD) to basic concepts of the genre poem, interdisciplinarity (activities related to the areas of Arts And geography) and transdisciplinarity (addressing cultural and environmental issues), in order to prove that it is possible to develop a multimodal work that focuses on improving the quality of education through actions in which the greatest beneficiaries will be the students who will become habitual literary readers . The research had as literary corpus the work Impregnations in the forest, Amazonian poems of Helena Parente Cunha, worked with students of 6º and 9º. Year of Primary Education, in the light of the theoretical foundations of educators Bordini and Aguiar, Bortoni-Ricardo, Antônio Candido, Alfredo Bosi, Roxane Rojo, among others. The applied methodology was the semiological one of Bordini and Aguiar, where, from a book of poems, the reading of the poems was explored in interface with the cinematographic reading of the film Tainá, an adventure in the Amazon, production of Pedro Carlos Rovai, directed By Sergio Bloch, resulting in a book and a CD containing respectively the poems of the work Impregnations in the forest, Amazonian poems by Helena Parente Cunha, illustrated (drawing and painting) and audio (oralized and recorded reading).